Faktor-faktor yang Mendorong Inovasi Frugal : Kondisi di India dan Prospek di Indonesia - Karlina Sari; Kusnandar Kusnandar (STI Policy and Management Journal, 2012)
Tighter competition in global market encourages every firm to innovate to produce high-quality products, but with affordable price for most group of consumers. Some local Indian firms, such as Tata Motor, Tata Chemical; and some foreign subsidiary firms, such as General Electric and Hindustan Unilever Ltd; have been succeeded in conducting innovation, producing technology-based products in more compact size and cheaper price compared to the conventional ones. In academic world, this kind of innovation is known as frugal innovation. Basically, frugal means not only cheap price but also how a product is designed, produced, distributed, and maintained based on its function, in regards with resources constraints. As innovation in Indonesia is often constrained by cost factor, frugal innovation would be appropriate for this country. Macro condition and supporting government policy are highly matters for the implementation of frugal innovation. The objectives of this study are to explore supporting factors of frugal innovation in India and to analyze the prospect of its implementation in Indonesia through comparison of those supporting factors between the two countries. Thus, this study uses comparative analysis. Literature review shows that supporting factors of frugal innovation in India are entrepreneurship, technology-based and innovation-based industry, vast domestic market, dominant low-middle-income population, openness toward foreign direct investment, and government support. Comparing the condition of India and Indonesia, frugal innovation is highly prospective to be implemented in Indonesia if technology and innovation-based industries are strengthened and government provides and implement effective policies.